PENGARUH NILAI BAHASA INDONESIA TERHADAP NILAI MATEMATIKA SISWA KELAS VIII MTs N BLORA - Claudia Vironica Ayu Viranda; Dwi Hardiyanto; Dwi Yulia Ningsih; Indhi Asokawati; Kholidatul Muna; Panji Maulana Majid; Dewi Wulandari (Jurnal Riset Pembelajaran Matematika, 2023)
Indonesian is one of the main subjects taught in schools. This is because students' Indonesian language skills can support success in all fields of study. One of them is Mathematics. Even though Indonesian and Mathematics at first glance look different, the fact is that the two subjects are related to each other. The purpose of this research is to prove the influence of Indonesian language scores on mathematics scores. The research was conducted at MTs N Blora which is located at Jalan Turirejo KM 0.5, Turirejo, Kec. Japan, Kab. Blora, Central Java Province. Where this research was carried out for 29 days, from December 1 to December 29 2022. With the target or targets, namely class VIII students of MTs N Blora. In this study, we used a type of quantitative research. By collecting data based on written documents in the form of data on Mathematics and Indonesian Language scores. This value can be seen in the odd semester PTS scores 2022/2023. Data analysis used is Descriptive Statistical Analysis and Simple Regression Analysis. From the results of the study, a simple linear regression equation was determined, namely Y = 22.375 + 0.751 X . The explanation is that if the value of Indonesian (X) increases by 1 (unit), then the value of Mathematics (Y) will increase by 0.751. Based on the analysis, it can be concluded that Indonesian language skills have a significant influence on the mathematics of class VIII MTs N Blora. Because Indonesian language subjects are the main subjects taught in schools, where students' Indonesian language skills can later support success in all fields of study. One of them is Mathematics.